2018
DOI: 10.1097/mog.0000000000000432
|View full text |Cite
|
Sign up to set email alerts
|

Liver disease in patients with cystic fibrosis

Abstract: A better understanding of the pathophysiology of disease is critical to developing more disease-specific diagnostics and therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 33 publications
0
48
0
2
Order By: Relevance
“…A previous study demonstrated that hepatic cytochrome P450 expression is reduced in rats subjected to DSS-induced colitis via LPS-induced downregulation [79]. Patients affected by cystic fibrosis lack the function of the cystic fibrosis transmembrane conductance regulator (CFTR), which is involved in bile flow and alkalinization, and may develop liver damage due to chronic cholestasis [80]. DSS-induced colitis has been demonstrated to cause biliary injury in Cftr knockout mice, which could be reversed by antibiotic treatment, and not by bile induction, via administration of 24-nor-ursodeoxycholic acid [81].…”
Section: Figurementioning
confidence: 99%
“…A previous study demonstrated that hepatic cytochrome P450 expression is reduced in rats subjected to DSS-induced colitis via LPS-induced downregulation [79]. Patients affected by cystic fibrosis lack the function of the cystic fibrosis transmembrane conductance regulator (CFTR), which is involved in bile flow and alkalinization, and may develop liver damage due to chronic cholestasis [80]. DSS-induced colitis has been demonstrated to cause biliary injury in Cftr knockout mice, which could be reversed by antibiotic treatment, and not by bile induction, via administration of 24-nor-ursodeoxycholic acid [81].…”
Section: Figurementioning
confidence: 99%
“…A study aiming to identify patients with early fibrosis in CFLD demonstrated that vibration‐controlled transient elastography could differentiate patients with CFLD from those without CFLD (8.2 versus 4.5 kPA with an area under the curve of 0.91). It also found that an increase of >0.38 kPA/year in scores could identify those at greatest risk for progression . Incorporating transient elastography results into the NC improved the specificity and positive predictive value to diagnose CFLD, but sensitivity was limited because some degree of fibrosis was needed before the test results were positive for CFLD.…”
Section: Diagnosis Management and Treatment Of Liver Disease In Cfmentioning
confidence: 99%
“…It also found that an increase of >0.38 kPA/year in scores could identify those at greatest risk for progression. (29,30) Incorporating transient elastography results into the NC improved the specificity and positive predictive value to diagnose CFLD, (7) but sensitivity was limited because some degree of fibrosis was needed before the test results were positive for CFLD. On the basis of these data, we implemented a protocol in our lung transplant program to screen all patients with CF for liver disease (Tables 1 and 2).…”
Section: Fibrosis Assessmentmentioning
confidence: 99%
“…84 This is a biliary tract epithelium-based cirrhosis that presents most frequently in teenagers, though it can occur de novo later in life. 85 Screening for liver disease is undertaken annually by the measurement of transaminases and the ultrasound/fibroscan imaging of the liver, though there is no strong evidence that this changes outcomes. 47 Management of CF-related liver disease should be in collaboration with an experienced hepatologist as it is a progressive condition that may ultimately require transplantation.…”
Section: Other Organ Diseasesmentioning
confidence: 99%